Fructooligosaccharides synthesized by fructosyltransferase from an indigenous coprophilous Aspergillus niger strain XOBP48 exhibits antioxidant activity. (October 2020) - Ojwach, Jeff; Kumar, Ajit; Mukaratirwa, Samson; Mutanda, Taurai
Abstract: Fructooligosaccharides (FOS) produced via sucrose biotransformation by partially purified Fructosyltransferase (Ftase) from an indigenous coprophilous Aspergillus niger strain XOBP48 ( An XOBP48) are reported to have antioxidant and nutraceutical properties in the present study. The Ftase activity on sucrose yielded FOS identified as monomeric glucose, 1- kestose (GF2 ), and 1, 1– kestotetraose (GF3 ) which were further purified and quantified using HPLC-RI system. The antioxidant activities of purified FOS at concentrations of 1, 1.5, 3, 6, 12, 24 and 48 μg/ml were determined by applying three experimental models and comparing their properties with FOS standards and vitamin C. The free radical scavenging activity measured by 1, 1 - diphenyl-2-picryl hydroxyl (DPPH) assay, ferric reducing antioxidant power (FRAP) assay and nitric oxide (NO) radical inhibition assay, yielded IC50 values of 2.6 μg/ml, 3.9 μg/ml and 3.4 μg/ml, 3.8 μg/ml and 0.69 μg/ml, 0.74 for purified GF2 and GF3, respectively. The free radical scavenging and inhibition activities showed a concentration dependent antioxidant activity of purified FOS with no significant differences as compared to the standards p  < 0.01 and vitamin C. In conclusion, the results demonstrated that purified FOS could be exploited in biotechnological applications and/or as to be used as functional ingredients in commercial products such as the production of nutraceutical compounds due to their potential antioxidant properties. Graphical abstract: Image 1 Highlights: Isolation of coprophilous fungus Aspergillus niger strain XOBP48 is able to produce Fructooligosaccharides. Synthesis of Fructooligosaccharides by Fructosyltransferase enzyme. Biotransformation of sucrose to Fructooligosaccharides. Quantification of Fructooligosaccharides by HPLC-RI were identified as 1, 1, 1-kestopentaose, 1-kestose and 1, 1-kestoteraose. Antioxidant Assays using DPPH, FRAP and NO.